Cross Talk Among Calcium, Hydrogen Peroxide, and Nitric Oxide and Activation of Gene Expression Involving Calmodulins and Calcium-Dependent Protein Kinases in Ulva Compressa Exposed to Copper Excess - Moenne-Munoz, A; Morales-Munoz, B; Contreras-Arredondo, R; Gonzalez-Figueroa, A (2012)
Sin Editorial Disponible